Coral spawning patterns in the Gulf of Thailand reveal synchronised annual daytime spawning, with a review of spawning patterns in Pavona corals across the Indo-Pacific - Rahul Mehrotra; Suppakarn Jandang; Coline Monchanin; Matthias Desmolles; Lalita Putchim; Natchanon Kiatkajornphan; Supatcha Japakang; Anne Groenevelde; Morokot Long; Matthew Glue; Anchalee Chankong; Nitchanan Nilkerd; et al. (PLoS ONE, 2026)
Global documentation of coral spawning has been increasing, yet remains restricted to corals and reefs for which established patterns have largely been identified, being overwhelmingly associated with periods of darkness after sunset. With this increase in geographic representation has come a growing number of spawning observations that skew or directly challenge previously established trends. After multiple incidental observations of daytime spawning of Pavona corals in the Gulf of Thailand, we aimed to establish spawning patterns for Pavona in the region using non-invasive surveys. Here we document synchronous daytime coral spawning for the species Pavona explanulata and P. varians across over 450 km of coastline along the Eastern Gulf of Thailand and Cambodia. Data collected via observation-only SCUBA surveys over a five-year period identified contrasting patterns of spawning timing of these corals from most other taxa for which data is available in the Gulf of Thailand, based on time of the year, proximity to the lunar peak and hours after sunrise. Based on a null-dataset of reef surveys with an absence of spawning, we were able to add credence to a restricted spawning period of these corals to being typically between September and December in the Gulf, with a sequential spawning of P. explanulata after P. varians with minimal overlap. We identified a consistently predictable onset of gamete release approximately between 6–8 hours after sunrise for P. varians and 7–9.5 hours for P. explanulata . We therefore conducted a review of spawning timing and patterns for Pavona corals across the globe identifying considerable variation across taxa and regions with support for high synchronicity within biogeographic regions. Finally, our dataset also incidentally documented additional cases of synchronised daytime gamete release from Cycloseris and Porites corals highlighting the need for further study on the dynamics of daytime gamete release.